“Guyub” as a Mediator Between Facilitative Leadership and Global Mindset: A Study of Indonesian State-Owned Enterprises (SOEs): [“Guyub” Sebagai Mediator Hubungan Antara Kepemimpinan Fasilitatif dan Kesiapan Global: Studi Badan Usaha Milik Negara (BUMN) Indonesia] - Murniati, Juliana; Sutamto, Edwin (Faculty of Psychology, Universitas Surabaya, 2023)
Indonesian State-Owned Enterprises (SOEs) have strategic positions in a number of economic sectors, making it pioneers of Indonesian global excellence. Along with the visions it holds, the leaders of Indonesian State-Owned Enterprises (SOEs) must be reliable in business management, always respecting local Indonesian sensibilities. Within the framework of providing an empirical basis in leadership development, this study was aimed at exploring the relationship of facilitative leadership with global mindset, through Indonesian standard culture mediator, in the form of “guyub”. The correlational study, utilizing quantitative analysis, was conducted with 202 employees of two Indonesian State-Owned Enterprises (SOEs). The mediational analysis by Baron and Kenny (1986), with the testing of the scales of influence using Sobel test, showed that facilitative leadership significantly supported global mindset through “guyub”, although the mediating effect was only partial. The implications of the results of this study, for State-Owned Enterprises (SOEs), was the need for the acceleration of the provision of intellectual capital (IC) to achieve optimal ability in managing the global uniformity of businesses, markets, and cultures. Two other forms of capital, i.e., social capital (SC) and psychological capital (PC), as the results of domestic multiculturalism, need to be transformed into global uniformity, by the development of intercultural sensitivity as an active component. Badan Usaha Milik Negara (BUMN) memiliki posisi strategis di sejumlah sektor ekonomi yang menjadikannya sebagai pelopor keunggulan global Indonesia. Sejalan dengan visi yang dimiliki, pemimpin Badan Usaha Milik Negara (BUMN) harus handal dalam mengelola bisnis, dengan tetap menjunjung kearifan lokal Indonesia. Dalam rangka menyediakan dasar empiris dalam pengembangan kepemimpinan, studi ini bertujuan untuk mengeksplorasi hubungan kepemimpinan fasilitatif, dengan kesiapan global melalui mediator budaya standar Indonesia berupa “guyub”. Studi korelasional dengan analisis kuantitatif dilaksanakan pada 202 karyawan dua Badan Usaha Milik Negara (BUMN) di Indonesia. Analisis mediasi Baron dan Kenny (1986) dengan pengujian besaran pengaruh melalui uji Sobel menunjukkan kepemimpinan fasilitatif signifikan mendorong kesiapan global melalui mediator guyub, namun efek mediasinya bersifat parsial. Implikasi hasil studi ini bagi Badan Usaha Milik Negara (BUMN) adalah perlunya mengakselerasi intellectual capital (IC) agar kemampuan dalam mengelola keberagaman bisnis, pasar, dan budaya secara global menjadi optimal. Dua kapita lainnya, social capital (SC) dan psychological capital (PC), sebagai hasil dari multikulturalisme domestik, perlu ditransformasi menjadi keberagaman global, dengan mengembangkan sensitivitas antar budaya sebagai komponen aktif.